2001
DOI: 10.1046/j.1365-2958.2001.02492.x
|View full text |Cite
|
Sign up to set email alerts
|

The ratio between CcdA and CcdB modulates the transcriptional repression of the ccd poison–antidote system

Abstract: SummaryThe ccd operon of the F plasmid encodes CcdB, a toxin targeting the essential gyrase of Escherichia coli, and CcdA, the unstable antidote that interacts with CcdB to neutralize its toxicity. Although work from our group and others has established that CcdA and CcdB are required for transcriptional repression of the operon, the underlying mechanism remains unclear. The results presented here indicate that, although CcdA is the DNA-binding element of the CcdA -CcdB complex, the stoichiometry of the two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
142
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 31 publications
6
142
1
1
Order By: Relevance
“…2). In both cases, it was observed that DNA binding of the CcdAB complex was decreased in the presence of excess 100TCcdB, as described previously for WT CcdB (14). It can also be seen that the complex of 100TCcdB with CcdA (lanes 6-8, Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2). In both cases, it was observed that DNA binding of the CcdAB complex was decreased in the presence of excess 100TCcdB, as described previously for WT CcdB (14). It can also be seen that the complex of 100TCcdB with CcdA (lanes 6-8, Fig.…”
Section: Resultssupporting
confidence: 85%
“…In either event, the free WT CcdB could then bind to its cellular target, DNA gyrase, resulting in growth inhibition or cell death. Alternatively (or in addition), an increase in the CcdB:CcdA ratio as a result of mutant expression could lead to derepression of the ccd operon and fresh synthesis of CcdA and WT CcdB (14). The fresh CcdA would bind to the excess, inactive mutant of CcdB and the newly synthesized CcdB could bind to its cellular target, DNA gyrase.…”
Section: Resultsmentioning
confidence: 99%
“…Under conditions of stress, the labile antitoxin is degraded. The resulting increase in the toxin/antitoxin ratio leads to transient derepression of the operon and fresh synthesis of both antitoxin and toxin (9). In the case of the ccdAB system on F-plasmidcontaining cells, the toxin CcdB is expressed along with its unstable antidote, CcdA, forming a TA complex.…”
Section: Abstract Toxin-antitoxin Persistencementioning
confidence: 99%
“…Cellular stress leads to an increase in toxin protein accumulation, most likely from antitoxin degradation. Specific toxin proteins such as RelE, Doc, and CcdA have been proposed to function as either transcriptional co-repressors, as part of the TA complex, or as de-repressors, which are dependent upon changes in the toxin-antitoxin ratios (25)(26)(27)(28)(29). Transcriptional de-repression is thought to occur by a mechanism in which excess toxin interacts with and destabilizes the TA-DNA repressor complex (25,26,29).…”
mentioning
confidence: 99%